The Risk of Acute Kidney Injury and Its Impact on 30-Day and Long-Term Mortality after Transcatheter Aortic Valve Implantation - Katrin Gebauer; Gerhard-Paul Diller; Gerrit Kaleschke; Gregor Kerckhoff; Nasser Malyar; Matthias Meyborg; Holger Reinecke; Helmut Baumgartner (International Journal of Nephrology)
Background. Transcatheter aortic valve implantation (TAVI) is widely used in high risk patients (pts) with aortic stenosis. Underlying chronic kidney disease implicates a high risk of postprocedural acute kidney injury (AKI). We analyzed its occurrence, impact on hospital stay, and mortality. Methods. 150 consecutive pts underwent TAVI in our institution (mean age 81 ± 7 years; logistic EuroSCORE 24 ± 15%). AKI definition was a creatinine rise of 26.5 μmol/L or more within 48 hours postprocedural. Ten patients on chronic hemodialysis were excluded. Results. AKI occurred in 28 pts (20%). Baseline creatinine was higher in AKI pts (126.4 ± 59.2 μmol/L versus 108.7 ± 45.1 μmol/L, P=0.09). Contrast media use was distributed evenly. Both, 30-day mortality (29% versus 7%, P<0.0001) and long-term mortality (43% versus 18%, P<0.0001) were higher; hospital stay was longer in AKI pts (20 ± 12 versus 15 ± 10 days, P=0.03). Predicted renal failure calculated STS Score was similar (8.0 ± 5.0% [AKI] versus 7.1 ± 4.0% [non-AKI], P=0.32) and estimated lower renal failure rates than observed. Conclusion. AKI remains a frequent complication with increased mortality in TAVI pts. Careful identification of risk factors and development of more suitable risk scores are essential.